A six sigma case study in a large-scale auto motive supplier company in Turkey - Tanık, Murat (My University, 2012)
Although six sigma is a really effective methodology with its strong data-based decision-making aspect, there are many obstacles and factors that weaken the effectiveness of the projects. This fact is even more obvious in the heavy industry, especially in developing countries such as Turkey, where statistical insight is not very common and systematic approaches are often neglected. Belief systems, culture, knowledge level of data-based decision-making or to put it simply, human factor and its management are the most crucial factor for success. Different cultures and different work environments impose the need for discovering new ways for altering the beliefs and improving the motivation of the project participants. The responsibility of changing the perception of team members lies on the shoulders of quality leaders. The purpose of this study is to highlight some important points that can contribute to the success and effectiveness of future six sigma programmes via data obtained from a number of projects that were carried out in a large automotive supplier in Izmir, Turkey. The authors participated in the programme as project consultants and authors’ observations from management meetings, training courses, and the project meetings are reflected and many key findings are mentioned in the paper.
Keywords: six sigma; project effectiveness; statistical training for industry